DIFFERENTIAL EXPRESSION OF BDNF, MIR-206 AND MIR-9 UNDER THE CHRONIC ETHANOL EXPOSURE AND ITS WITHDRAWAL - Aydin Sinirlioglu, Zeynep; AKBAŞ, FAHRİ; AKBAŞ, FAHRİ (My University, 2016)
Chronic and acute alcohol abuse results in alters in the expression of some miRNAs and their mRNA targets in specific area of the brain. These expression changes might cause the cellular adjusments to long term alcohol abuse. We searched BDNF, miR-9 and miR-206 expression changed in SH SY5Y cell following exposure to ethanol and withdrawal. These miRNAs and BDNF are estimated to target genes of alcoholism. Chronic ethanol exposure and its removal showed that specific changes in miRNA and BDNF expression in cell line advocating that different expressions could be evoked with different exposure conditions. Especially, there were three group in our experiment one of them 10 days Chronic ethanol exposure, other one 5 days chronic ethanol exposure then 5 days normal medium without ethanol for withdrawal period and other group was control. After all, mir-9 was up-regulated after ethanol treatment but was downregulated in withdrawal condition. In addition mir-206 was up-regulated all condition. Whereas BDNF gene expression was regulated opposite direction according to miRNA expression. Our results suggest that a possible role of differentially expressed miRNAs and BDNF perform together in mediating alcohol influence.